Central America (Journal of Parents and Teachers, 2026)
Central America is the bridge between two worlds. It is made up of Guatemala, El Salvador, Honduras, Nicaragua and Costa Rica. Panama can be considered separately due to its geopolitical reality, as can Belize, which was colonised by Great Britain. Before the arrival of the Spanish, Central America was the cradle of Mayan civilisation. After independence, it was constituted as a single country, a unitary project that did not last. Currently, the countries of Central America are striving for peace and development.
Keywords: Central America; conquest; independence; unification project